2013
DOI: 10.1177/0363546512472975
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Lateral Epicondylitis With Platelet-Rich Plasma, Glucocorticoid, or Saline

Abstract: Neither injection of PRP nor glucocorticoid was superior to saline with regard to pain reduction in LE at the primary end point at 3 months. However, injection of glucocorticoid had a short-term pain-reducing effect at 1 month in contrast to the other therapies. Injection of glucocorticoid in LE reduces both color Doppler activity and tendon thickness compared with PRP and saline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(190 citation statements)
references
References 57 publications
3
182
1
4
Order By: Relevance
“…Peerbooms et al demonstrated a significant improvement in treating lateral epicondylitis with PRP vs. steroid injection: PRP demonstrated superiority up to 1 year posttreatment, with results remaining stable by the two-year mark [30]. A recent study suggested there is a negligible difference in treatment effectiveness between PRP, cortisone, and saline injections at 12 weeks posttreatment [31]. With this technique utilized, a high volume of lidocaine (10-15 ml) was injected into the paratenon prior to treatment which could adversely affect the outcome.…”
Section: Tendon Pathologymentioning
confidence: 99%
“…Peerbooms et al demonstrated a significant improvement in treating lateral epicondylitis with PRP vs. steroid injection: PRP demonstrated superiority up to 1 year posttreatment, with results remaining stable by the two-year mark [30]. A recent study suggested there is a negligible difference in treatment effectiveness between PRP, cortisone, and saline injections at 12 weeks posttreatment [31]. With this technique utilized, a high volume of lidocaine (10-15 ml) was injected into the paratenon prior to treatment which could adversely affect the outcome.…”
Section: Tendon Pathologymentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The most common reasons for exclusion were review paper (53), non-tendinopathy (14), injection of active control (7; eg, whole blood, PRP) and non-randomised study (7). Several manuscripts were excluded from this review because they were superseded by papers from the same study with longer follow-up including de Vos et al 29 30 and Peerbooms et al 31 A flow diagram of study identification and selection is shown in figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Several major clinical studies have examined the role of PRP in the treatment of lateral epicondylitis (Table 1) [4044]. One of the earliest investigations was a cohort study of 20 patients who had refractory lateral epicondylitis for a mean of 15 months and all of them were considering surgical intervention.…”
Section: Autologous Blood Preparationsmentioning
confidence: 99%